Algebra of Polynomials by H. Lausch, W. Nobauer By H. Lausch, W. Nobauer

Similar mathematics books

Introduction to computer performance analysis with Mathematica

"Introduction to machine functionality research with Mathematica" is designed as a beginner's advisor to machine functionality research and assumes just a simple wisdom of desktops and a few mathematical talent. The mathematical features were relegated to a Mathematica application disk, permitting readers to aim out lots of the suggestions as they paintings their method in the course of the ebook.

Extra resources for Algebra of Polynomials

Sample text

N,, a,). This establishes the theorem. 2. Let G be a group we will regard as an algebra of 23 and suppose X = {x,, . , xk}. We write G(X, 53) = G[x,, . , xk] and want to find a normal form system for this algebra. Again we first simplify our nota- 30 POLYNOMIALS AND POLYNOMIAL FUNCTIONS CH. 1 tion. Let M be the additive group of integers and M k the direct product of k copies of M . (0, 0, . ,0) E M k will be denoted by 0. An ordered pair (i,, . , i,), (Z, . , 1,) of elements of M k is called reducible if, for some index v, i, f 0, iv+l = iV+,= .

WnP1)w,. If w1 = . . = w, = w, we write wl... w,,= w", and set wo = 1 . Then ( a n y ) + . . (alx)+ao, a, E R, v = 0, . . , n, is a well. . +alx+a,. 11. Theorem. Let % betheset of all words a n y + . . +a,x+ao where n a 0, a,€ R , for t = 0, . , n, and a,, # 0. Then %U{O} is a normal form system of R [ x ] . Proof. 11. a) We have to show that, for every representation p = w(a,, x ) of an element p E R [ x ] ,we can find a word in % representing p , in a finite number of steps. We proceed by induction on the minimal rank r of w ( a , x).

Ug-l = 0, else the polynomial U , - ~ X ~ - ~ +. . u,x+ uo would have at most q-1 different roots, a contradiction. e. Q is 1-polynohially complete. The functions P,-~&) t~-l+p,&) 5;-,+ . . (&)E PI@), 2’ = 0, . , q - 1, are functions of P,(Q). (51) 5; c 0 = v=q-1 6;. r”(E1) § 12 SOME EXAMPLES OF POLYNOMIALLY COMPLETE ALGEBRAS Let a € Q be arbitrary, then 0 ,,=q-l p,(a) ti 0 = v=q-1 39 r,(a) ti, and by the argument from above we conclude p,(a) = rv(a), v = 0, . e. p,(5,) = r&), v = 0, . , q- 1.